A Review of Optimum Sizing Techniques for Off-Grid Hybrid PV-Wind Renewable Energy Systems - Al Busaidi, Ahmed Said (International Journal of Students’ Research in Technology & Management, 2015)
Hybrid renewable energy power systems have proven their ability to address limitations of single renewable energy system in terms of power stability, efficiency and reliability while running at minimum cost.Â In the present decade, lots of research and practical experiences have been done.Â This paper will present an overview of the different hybrid solar (PV)- windÂ renewable energy systems for power generations. Different criteria of selecting the right sizing of different component of hybrid renewable energy power plant at the most preferable economical, logistical environmental considerations will be discussed. In some cases when the weather data are not available, this paper will discuss some optimization approaches which are used to compare the performance and energy production cost of different system configurations using simulation techniques. Based on the fact that, potential of the wind and solar energy is not equal in Oman, this paper will discuss the optimum sizing process of two proposed hybrid solar-wind plants in Oman.